International effects of a compression of euro area yield curves - Feldkircher, Martin; Gruber, Thomas; Huber, Florian (Journal of Banking & Finance, 2020)
In this paper, we use a Bayesian global vector autoregressive model to analyze the macroeconomic effects of a flattening of euro area yield curves. Our findings indicate positive effects on real activity and prices, both within the euro area as well as in neighboring economies. Spillovers transmit through an exchange rate channel and a broad financial channel. We complement our analysis by conducting a portfolio optimization exercise. Our results show that multi-step-ahead forecasts conditional on the euro area yield curve shock improve Sharpe ratios relative to other investment strategies.